Cell Biology of Galectins - Timoshenko, Alexander (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Galectins are a family of soluble beta-galactoside-binding proteins with diverse glycan-dependent and glycan-independent functions outside and inside the cell. There are sixteen recognized mammalian galectin genes, and their expression profiles are very different between cell types, tissues, and species. This Special Issue covers recent progress in the field of the cell biology of galectins, relevant concepts of galectin regulatory mechanisms, and biomedical aspects of these unique multifunctional proteins.